2019
DOI: 10.1002/syn.22133
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic control of Drosophila neuromuscular junction function

Abstract: The ability to adapt to changing internal and external conditions is a key feature of biological systems. Homeostasis refers to a regulatory process that stabilizes dynamic systems to counteract perturbations. In the nervous system, homeostatic mechanisms control neuronal excitability, neurotransmitter release, neurotransmitter receptors, and neural circuit function. The neuromuscular junction (NMJ) of Drosophila melanogaster has provided a wealth of molecular information about how synapses implement homeostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 94 publications
(246 reference statements)
0
65
0
Order By: Relevance
“…This phenomenon has been described in a variety of systems, including the mammalian central nervous system and the Drosophila neuromuscular junction (NMJ). The HSP at the Drosophila NMJ appears mechanistically distinct from HSP in the mammalian CNS, and therefore will not be covered here (for reviews of this topic see Davis and Müller, 2015;Frank et al, 2020). It should be noted, however, that both innate immune molecules and glia have recently been implicated in HSP at the Drosophila NMJ (Harris et al, 2015;Wang et al, 2020).…”
Section: Homeostatic Synaptic Plasticity (Hsp)mentioning
confidence: 99%
“…This phenomenon has been described in a variety of systems, including the mammalian central nervous system and the Drosophila neuromuscular junction (NMJ). The HSP at the Drosophila NMJ appears mechanistically distinct from HSP in the mammalian CNS, and therefore will not be covered here (for reviews of this topic see Davis and Müller, 2015;Frank et al, 2020). It should be noted, however, that both innate immune molecules and glia have recently been implicated in HSP at the Drosophila NMJ (Harris et al, 2015;Wang et al, 2020).…”
Section: Homeostatic Synaptic Plasticity (Hsp)mentioning
confidence: 99%
“…PHP is a well-studied form of homeostatic plasticity at the Drosophila NMJ. Here, rapid pharmacological or chronic genetic manipulations that diminish postsynaptic GluR functionality trigger a trans-synaptic retrograde signaling system that homeostatically increases presynaptic glutamate release to maintain stable synaptic strength (Frank et al, 2020 ). Recently, it was demonstrated that GluR knockdown specifically on muscle 6 can trigger PHP selectively at the subset of synapses innervating muscle 6 without influencing transmission at the synaptic terminals of the same motor neuron that innervate the adjacent muscle 7 (Li et al, 2018a ), demonstrating a remarkable degree of compartmentalized expression of PHP.…”
Section: Resultsmentioning
confidence: 99%
“…Presynaptic homeostatic potentiation (PHP) is a well-studied form of homeostatic plasticity at the Drosophila NMJ. Here, rapid pharmacological or chronic genetic manipulations that diminish postsynaptic GluR functionality trigger a trans-synaptic retrograde signaling system that homeostatically increases presynaptic glutamate release to maintain stable synaptic strength (Frank et al, 2020). Recently, it was demonstrated that GluR knockdown specifically on muscle 6 can trigger PHP selectively at the subset of synapses innervating muscle 6 without influencing transmission at the synaptic terminals of the same motor neuron that innervate the adjacent muscle 7 (Li et al, 2018a), demonstrating a remarkable degree of compartmentalized expression of PHP.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shed light on how neurotransmission is stabilized when synaptic growth and function is challenged (Davis and Muller, 2015; Frank et al, 2020; Goel et al, 2019a; Goel et al, 2019b; Li et al, 2018b). However, less is known about how this stability is maintained when neuronal terminals confront diverse and even opposing challenges in synaptic growth and function.…”
Section: Discussionmentioning
confidence: 99%